(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Copper metal with chelating ligands forms coordination complexes. Copper (II) exists [Cu (H2O)6]2+ in an aqueous medium. Copper (II) complex shows the fastest water exchange rate for any transition metal aqua complex. In this paper, we studied the biology of Schiff base and its copper complexes. In this paper, we presented the results of synthesis and characterization studies for the Schiff’s base transition metal complexes involving Schiff’s ligands. The implemented methodologies for the synthesis of metal complexes are self-assembly method. The IR spectra reveal the existence of functional groups and anionic ligands such as O-H (water), C=C, C=N, and N3 frequencies. The UV spectra confirm the complexation of metal and ligand with the increase in the absorbance value compared to the free ligand. The max values of the d-d band are observed to be in the range of 300 to 321 nm.